Obesity in black and white: Accounting for 19th century US BMI differences by socioeconomic status and biology - Scott A. Carson (Center for Economic Studies and ifo Institute (CESifo), 2012)
Little research exists on late 19th and early 20th century US body mass index value differences by race, and darker complexions were associated with greater BMI values. Mulattos had greater BMI returns associated with socioeconomic characteristics, indicating that while blacks had greater BMIs than fairer complexioned whites and mulattos, part of the difference was offset by socioeconomic characteristics that favored fairer complexions. Black, mulatto, and white BMIs declined between 1860 and 1920, and farmers had greater BMIs than workers in other occupations.
Keywords: I10; J11; J71; N31; 330; nineteenth century US race relations; body mass index; biological inequality